Β-Amyrin supplementation ameliorates the toxic effect of glycerol in the kidney of rat model. (July 2020) - Hashish, EA; Elgaml, SA; El-fattah, AHA; Shalaby, SI; Abdelaziz, S
Acute kidney injury (AKI) is a common life-threatening complication. In this study, β-amyrin is hypothesized to exert a potential nephroprotective effect against glycerol-induced nephrotoxicity in rats. Thirty-two female Sprague-Dawley rats were divided into four groups: normal control, β-amyrin treated (50 mg kg −1 body weight) for 14 days, glycerol 25% (10 ml kg −1 BW volume/volume in sterile saline, intramuscular), and β-amyrin + glycerol-treated rats. Assessing kidney function was done through the measurement of serum urea and creatinine (SCr). Real-time quantitative polymerase chain reaction analysis was done to measure the changes in the gap junction protein and intermediate filament proteins (IFPs) messenger RNA (mRNA) levels. Renal tissue histopathology was also observed. Glycerol exhibited significant elevation in the SCr and urea with significant upregulation of connexin43, vimentin, and nestin. The levels of all disrupted parameters were improved by the pre-administration of β-amyrin. The β-amyrin exerts significant improvement of the biochemical parameters with a restoration of the renal tissue histopathological picture. Significant downregulation of the expression levels of the gap junction protein and IFPs mRNA was also seen. Collectively, the administration of β-amyrin showed a promising effect for a protection against glycerol-induced AKI in rats.